The Effect of Religious Education on Student Learning Achievement in Elementary Schools - Sya’bana, Mohammad Vega; Nisak, Sayida Khoiratun; Dr. Suryaningsih, S.S., M.Pd.K.; Rukiyanto, Bernardus Agus; Hastuti, Rini Mei (Academy of Education Journal, 2024)
The field of religious education has a pivotal function in the molding of students' character, morality, and ethical frameworks. Additionally, it facilitates an intimate grasp of the tenets and values espoused by various belief systems. The efficacy of teaching methods in education can have a notable impact on students' academic performance. Nevertheless, no research has been conducted at SDN Bhakti Karya to assess the impact of teaching methods in PAI on students' academic achievement. The objective of this study is to evaluate the impact of instructional approaches in Religious Education on students' academic performance at SDN Bhakti Karya. A qualitative approach was employed, whereby data were collected through interviews, observations, and document analysis. The findings indicate that effective teaching methods in Religious Education have a beneficial impact on students' academic achievement. Instructional methods that facilitate active engagement, the utilization of multimedia resources, group discussions, and the application of hands-on activities to comprehend religious concepts facilitate enhanced comprehension and the development of academic skills. Factors that facilitate the implementation of teaching methods include the provision of adequate facilities and infrastructure, as well as the training and development of competencies among teachers. However, obstacles such as time constraints and a curriculum that restricts the variety of teaching methods must also be addressed. In order to enhance students' academic performance, it is essential to reinforce facilities and infrastructure support, enhance teacher training, and assess the necessity and flexibility of the curriculum.